2021
DOI: 10.35848/1882-0786/abe80d
|View full text |Cite
|
Sign up to set email alerts
|

Insight into segregation sites for oxygen impurities at grain boundaries in silicon

Abstract: The three-dimensional distribution of oxygen atoms segregated at Σ9{114} grain boundaries (GBs) in Czochralski-grown silicon ingots is analyzed within a high spatial resolution of less than 0.5 nm by atom probe tomography combined with a focused ion beam (FIB) operated at −150 °C. The analysis reveals a segregation of oxygen atoms within a range of 2.5 nm across the GB plane, which is much narrower in comparison with the previous reports obtained using a conventional FIB. The oxygen concentration profile accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
2
4
1
Order By: Relevance
“…3). This result shows that the compositional modification at the GBs due to FIB irradiation can be suppressed by using LT-FIB technique, as reported [49,64,65]. Therefore, the concentration profile obtained by LT-FIB would significantly reflect the distribution of segregation sites, even though the impact of local magnification effects, about 0.5 nm in the segregation thickness [65], still remains.…”
Section: Segregation Sites At σ9{114} Gbs and σ9{111}/{115} Gbssupporting
confidence: 65%
See 1 more Smart Citation
“…3). This result shows that the compositional modification at the GBs due to FIB irradiation can be suppressed by using LT-FIB technique, as reported [49,64,65]. Therefore, the concentration profile obtained by LT-FIB would significantly reflect the distribution of segregation sites, even though the impact of local magnification effects, about 0.5 nm in the segregation thickness [65], still remains.…”
Section: Segregation Sites At σ9{114} Gbs and σ9{111}/{115} Gbssupporting
confidence: 65%
“…Figure 3(a) shows that the 1D profile of As concentration peaks slightly off the GB plane, similar to the 1D profile of oxygen concentration [65]. Comparing the 1D profile with the atomic arrangement in the GB revealed by HAADF-STEM (shown in Fig.…”
Section: Segregation Sites At σ9{114} Gbs and σ9{111}/{115} Gbssupporting
confidence: 60%
“…We also found that Σ3{113}/{557} GBs had a staircase‐like structure composed of nano‐facets of Σ3{111}/{111}‐like structure, similar to asymmetric Σ9{115}/{111} GBs, [ 55,56 ] in which the nano‐facet junctions were parallel to <1‐10>. Ab initio calculations revealed tensile bond strains of more than 2% along the nano‐facet junctions (Figure 6d), presumably due to long <110> reconstructed bonds, [ 57 ] and it would also act as dislocation sources. Actually, a number of dislocations are frequently generated at asymmetric GBs.…”
Section: Resultsmentioning
confidence: 93%
“…Then we analyze the stability and structural characteristics, dominated by electronic behaviors, via our ab initio local-energy and local-stress scheme [19][20][21][22][23] based on the Bader partitioning [24], in order to investigate the origin of stability/instability of each GB configuration in hcp Mg. As summarized in our review article [23], our scheme provides the distribution of local energy and local stress of each atom in a GB region as the response of valence electrons against local structural disorder, which was quite useful to understand the stability and property of GBs in Al [20,25], Fe [21,22,26,27] and Si [28,29]. This is the first application of our scheme to GBs in bivalent simple metals, of which the comparison with previous results in other materials is quite interesting.…”
Section: Introductionmentioning
confidence: 82%